A Solid‐Solution Approach to Mixed‐Metal Metal–Organic Frameworks – Detailed Characterization of Local Structures, Defects and Breathing Behaviour of Al/V Frameworks. Issue 26 (3rd September 2013) - Kozachuk, Olesia; Meilikhov, Mikhail; Yusenko, Kirill; Schneemann, Andreas; Jee, Bettina; Kuttatheyil, Anusree V.; Bertmer, Marko; Sternemann, Christian; Pöppl, Andreas; Fischer, Roland
Abstract: Invited for the cover of this issue is the group of Roland Fischer at Ruhr University Bochum. The cover image shows that the structure/properties of materials vary as the complexity of the framework is increased and different metals are combined in single‐phased MOFs Abstract : The biggest challenge in the presented work was using various analytical methods to understand the impact of doping with a second metal (V, in particular) and reveal the organization of these frameworks at the molecular level, which defines their properties... Read more about the story behind the cover in the Cover ProfileCover Profile and about the research itself onp. 4546 ff .